Women, gender equality and climate change - United Nations (2009)
Detrimental effects of climate change can be felt in the short-term through natural hazards, such as landslides, floods and hurricanes; and in the long-term, through more gradual deg radation of the environment. The adverse ef fects of these events are already felt in many areas, including in relation to, inter alia, ag riculture and food security; biodiversity and ecosystems; water resources; human health; human settlements and migration patterns; and energy, transport and industry. In many of these contexts, women are more vulnerable to the effects of climate change than men—primarily as they constitute the majority of the world’s poor and are more dependent for their livelihood on natural re sources that are threatened by climate change. Furthermore, they face social, economic and political barriers that limit their coping ca pacity. Women and men in rural areas in developing countries are especially vulnerable when they are highly dependent on local natural resources for their livelihood. Those charged with the responsibility to secure water, food and fuel for cooking and heating face the greatest challenges. Secondly, when coupled with unequal access to resources and to decision-making processes, limited mobility places women in rural areas in a position where they are disproportionately affected by climate change. It is thus important to identify gender-sensitive strategies to respond to the environmental and humanitarian crises caused by climate change.1
Keywords: 2000 à aujourd'hui; 2000-2009; changements climatiques; discipline; droit; développement international; environnement; femmes agricultrices; projet charge mentale; périodes historiques; santé; science politique et droit; sécurité alimentaire; thématiques; travail

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; périodes historiques; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppressions; thématiques; états-unis